Physical and Chemical Properties of the Agro-processing By-products Decomposed by Larvae of Musca domestica and Hermetia illucens(2) - BLOUKOUNON-GOUBALAN, ADIN YETON; SAIDOU, ALIOU; CHRYSOSTOME, CHRISTOPHE ACHILLE A. MAHUSSI; KENIS, Marc; AMADJI, LUCIEN GUILLAUME; Igué, A.M; MENSAH, GUY APOLLINAIRE (My University, 2019)
The present study aimed to assess the physical and chemical properties of the agro-processing by-products decomposed by fly larvae and to be promoted as soil amendment. The biodegradation process was performed using larvae of Musca domestica and Hermetia illucens during 30 days on corn bran, a mixture of soybean bran and corn bran (1:1 ratio), and a mixture of soybean bran and corn hull (8:2 ratio). The biodegradation by fly larvae was obtained by exposed the substrates to naturallyoccurring flies. Data on temperature, pH, fly larvae production, substrate weight, organic carbon, total nitrogen, nitrite and ammonia contents in the substrates were collected during the biodegradation process. Temperature ranged between 33 and 45 °C during the process and was higher in the mixture of soybean bran and corn hull while pH changed from neutral to alkaline. The substrate weight was reduced and a low carbon loss was recorded. The mixture of soybean bran and corn hull produced the highest amounts of fly larvae (38.28 g kg− 1 dry matter). Significant reductions (p < 0.05) of total nitrogen, ammonia and nitrite contents were recorded in the substrates. An increase of nitrite content in corn bran and in the mixture of soybean bran and corn bran starting from day 12 was observed. The final products of the biodegradation have a high total N content (from 53.75 ± 1.35 to 55.85 ± 0.87 g kg− 1) and provide suitable C:N and NH4- N:NO3-N ratios, suggesting that they can be used as high quality soil amendment.
Keywords: Soil fertility · Biodegradation · Organic residues quality · Crops’ residues · Benin